2017
DOI: 10.1128/jcm.00481-17
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Urinary Antibiograms Differ by Specific Patient Group

Abstract: Patients presenting to the emergency department (ED) represent a heterogeneous population comprised of all ages, various backgrounds, such as from the community and skilled-nursing facilities (SNFs), and at various risks for resistant pathogens. The aim of this study was to compare patient group-specific urinary antibiograms in the ED. Adults presented to the ED with an ICD 9/10 code urinary tract infection (UTI) diagnosis during July 2015 to June 2016 were randomly selected (n ϭ 500) to extract relevant demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…[24] Increasing resistance trends in US and Canada and lower susceptibility also support our finding. [4,12,25] b. Nitrofurantoin: It is an oral form, cheap, less side effects and most effective antibiotics which are commonly used in UTIs patients in our country. We have found that Nitrofurantoin is only 4.7% resistance to E coli in the present study and accounted the lowest resistance form antibiotics to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Increasing resistance trends in US and Canada and lower susceptibility also support our finding. [4,12,25] b. Nitrofurantoin: It is an oral form, cheap, less side effects and most effective antibiotics which are commonly used in UTIs patients in our country. We have found that Nitrofurantoin is only 4.7% resistance to E coli in the present study and accounted the lowest resistance form antibiotics to it.…”
Section: Discussionmentioning
confidence: 99%
“…[18,26,27] But less increasing resistance (from 0.7% to 0.9%) and higher susceptibility (>80%) in US support our report. [4,25] c. Ciprofloxacin: The quinolone derivative, Ciprofloxacin is used empirically not only in UTIs but also in various forms infections due to its safety profile and cheap in price. Its oral form is widely used in uncomplicated UTI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-implementation review of antimicrobial prescribing and outcomes for patients treated for UTI in the ED revealed substantial opportunity for improvement [ 6 , 12 ]. We therefore assembled a multidisciplinary working group comprised of the ASP team plus ED pharmacists and physicians to develop a best practice UTI empiric antimicrobial treatment algorithm for patients discharged directly from the ED.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore assembled a multidisciplinary working group comprised of the ASP team plus ED pharmacists and physicians to develop a best practice UTI empiric antimicrobial treatment algorithm for patients discharged directly from the ED. Antimicrobial therapy recommendations contained within the algorithm were based upon national and professional society guidelines, primary literature and findings from our background research characterizing the patient population, antimicrobial resistance patterns, prescribing behavior, and morbidity related to infection, as reported previously [ 2 , 4 , 6 , 12–27 ]. Several features of our algorithm are noteworthy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation